The Effect of Banana Stem Powder on the Productivity of the Brown Oyster Mushroom (Pleurotus cystidiosus) - Nurhayati, Rizky; Suparti, Suparti (BIOEDUSCIENCE, 2023)
Background: Brown Oyster Mushroom (Pleurotus cystidiosus) is a type of mushroom that has different advantages from other oyster mushrooms. Generally, farmers make planting media for brown oyster mushrooms made from sawdust of sengon wood. The availability of raw materials for sawdust of sengon wood is increasingly difficult to obtain. So we need other alternative materials as a source of nutrition, one of which is banana stem waste. This study aims to determine the effect of banana stem flour on the diameter of the cap, the number of fruiting bodies, and the wet weight of the fungus. Methods: This study used a completely randomized design (CRD) which consisted of one factor. This study used 4 treatments and 3 replications. Data was tested by quantitative descriptive analysis using the Analysis of Variance (ANOVA) test. Results: Banana stem flour has a significant effect on all parameters. The JM2 treatment resulted in a cap diameter of 10.3 cm, mushroom fruiting bodies of 10.6 and wet mushroom weight of 103.8 g. Conclusion: The addition of banana stem powder can increase productivity in the parameters of mushroom cap diameter, number of mushroom fruiting bodies, and wet weight of mushrooms, which can be used by readers or researchers. Utilization of waste such as sawdust of sengon wood and waste of banana fronds for the cultivation of brown oyster mushrooms is one way of handling plantation waste.